Bezlotoxumab. (18th July 2018) - Johnson, Stuart; Gerding, Dale N
Abstract : Bezlotoxumab, a monoclonal antibody directed against Clostridium difficile toxin B, is the first agent approved for prevention of C. difficile infection recurrence. This article reviews the development of bezlotoxumab and clinical trial data suggesting who may benefit most from this adjunctive therapy. Abstract: Clostridium difficile infection (CDI) is mediated by actions of toxin A and toxin B. Fully human monoclonal antibodies directed against the binding domains of these toxins were developed. Despite preclinical studies suggesting efficacy for the anti–toxin A monoclonal, actoxumab, the anti–toxin B monoclonal, bezlotoxumab, alone was shown to be effective in clinical trials. Intravenous infusion of bezlotoxumab at a 10 mg/kg dosage as adjunctive treatment reduced the risk of recurrent CDI over placebo for adult patients at increased risk for CDI recurrence in 2 large randomized, double-blind trials. Significant benefit was noted for patients with 1 or more of the following predefined risks: age >65 years, history of CDI, immunocompromise, severe CDI. Overall, bezlotoxumab appeared to be safe; however, an unexplained increased risk of heart failure was noted for patients with underlying congestive heart failure. Further refinement of who would benefit most and when best to administer bezlotoxumab is warranted.